Network analysis reveals overlapping roles of stakeholders related to seagrass-data provisioning in Indonesia - Sjafrie, Nurul Dhewani Mirah; Wicaksono, Pramaditya; Hernawan, Udhi E.; Triyono, Triyono; Yuwono, Doddy M.; Hafizt, Muhammad; Adi, Novi Susetyo; Ambo-Rappe, Rohani; Prayudha, Bayu; Selamat, Muhammad Banda; Sani, Sofia Yunia; Harahap, Setiawan Djody; et al. (Elsevier Ltd, 2023)
Seagrass data support conservation areas, carbon budget, natural resource assessment, and other national interests in Indonesia. However, to what extent seagrass-related data are available and how the data are managed are still unknown. In this study, we assess the status of data availability and the roles of stakeholders in seagrass-related data provisioning at a national level in Indonesia. Data were collected in August and September 2022 through Focus Group Discussion (FGD) and a questionnaire. The participants comprised representatives from the central governments (planning, ministerial, research, geospatial agencies), local governments, universities, and non-governmental organizations (NGOs) working in the fields related to the coastal ecosystem. Stakeholders’ roles were analyzed using Stakeholders’ Analysis (SA), while their relationships were examined with Social Network Analysis (SNA). The results showed that the seagrass areal extent (61.7) was the most crucial data needed, followed by the percent cover (12.77). Using seagrass data as coastal management was the highest priority among stakeholders. There were overlapping roles between stakeholders related to seagrass data, as producers or users, due to their urgent needs. Almost all stakeholders were key players, and there was a lack of coordination among them relating to seagrass data provisioning. There was an urgent need to strengthen seagrass data governance. The results of this work form an important pathway for Indonesia to develop approaches to map the seagrass areal extent and share knowledge. © 2023 Elsevier Ltd